The Role of Digital Innovation in Mediating the Influence of Digital Leadership and Digital Capability on Business Performance in the Event/ MICE Industry in Indonesia - Rachmat Ramadhan; Aekram Faisal; Willy Arafah (Dinasti International Journal of Education Management And Social Science, 2024)
The objective of this research is to analyze the influence of digital leadership and digital capability on business performance that was mediated by digital innovation in the event/MICE industry in Indonesia. The research utilized technical analysis of structural equation model (SEM), and bootstrapping method to analyze the mediation role. The population for the research is the owner or company leader of Event/ MICE organizers that has been operating for a minimum of 3 (three) years. The sample consisted of 236 respondents, selected by using the method of purposive sampling. The result of the research exhibited that the digital leadership and digital capabilities do not have direct positive influences on business performance. However, digital leadership and digital capabilities positively influence on business performance, after being mediated by digital innovation, and of the two, the digital capabilities have a greater influence on business performance. The study shows that digital leadership and digital capabilities have a positive influence on digital innovation and that business performance is positively impacted by digital innovation.  The practical implication of this research is the importance for management to enhance the role of digital leadership, digital capability and digital innovation to achieve better business performance.